TBX5 Mechanism of Action in Skeletal Muscle Cell Proliferation and Differentiation - Sheikh-Hassani, Massomeh (Université d'Ottawa / University of Ottawa, 2020)
Skeletal muscle development and function is governed by a conserved set of Transcription Factors (TFs) that regulate gene expression. The TF gene regulation is stimulus driven and cell-type and time point specific. TBX5 is an essential dosage sensitive regulator of heart and limb development. In the skeletal system, TBX5 is expressed in early stages in the lateral plate mesoderm and gives rise to the forelimb. TBX5 is also involved in proliferation and differentiation and survival pathways in both heart and limb development. Mutations in TBX5 gene lead to HOS which is characterized by various types of cardiac and musculoskeletal defects. TBX5 mechanism of action and its spatiotemporal function in skeletal muscle development has yet to be fully understood. TBX5 regulation is controlled through various factors such as alternative splicing, protein-protein interactions, Post-Translational Modifications (PTMs) and microRNAs. To date, many TBX5 interactors have been identified in cardiac cells however TBX5 protein interactors and target genes in skeletal muscle cells have not been studied. Understanding the protein interactome of TBX5 in skeletal muscle will enhance the current understanding of its mechanism of action. In this study we have characterized TBX5 with focus on its regulation, expression and biochemical properties in cardiac and skeletal muscle cells and moreover its mechanism of action specifically in skeletal muscle proliferation and differentiation. Chapter 1 discusses TBX5 regulation through alternative splicing leading to the existence of 5 distinct TBX5 isoforms with variable transcriptional activity, cardiac and limb expression pattern, biochemical properties and function. We show the pro-proliferation role of TBX5a in myoblasts while TBX5c shows to be pro-differentiation leading to the formation of myotubes in skeletal muscle C2C12 myoblasts. This opposing role of the two TBX5 isoforms lead us to studying TBX5 mechanism of action in proliferation and differentiation of skeletal muscle cells. In this study using a mass spectrometry-based approach we have identified novel TBX5 interacting partners in skeletal muscle cells for the first time by using stably overexpressed 3xFlag TBX5 via retroviral transduction in C2C12 cell line. Nuclear protein extracts were immunoprecipitated and sent for HPLC-ESI-MS/MS to identify potential protein partners of TBX5 in skeletal muscle cells. Moreover, the same stable cell line was used to identify TBX5 downstream target genes in these cell types by sending RNA extracts for microarray analysis. Amongst the 200 protein interactors identified, MYBBP1a and TBX5 interaction was confirmed and studied. The microarray analysis identified over 1200 differentially expressed genes and potential downstream targets of TBX5a from which Myostatin (Mstn) and Cyclin D2 (CcnD2) were both significantly upregulated and further confirmed and studied in relation to proliferation and differentiation in skeletal muscle cells. Chapter 2 focuses on the cooperative interaction between TBX5a and MYBBP1a inhibiting muscle specific gene promoter, Myogenin (MyoG). TBX5a and TBX5c seem to both interact with MYBBP1a but result in variable transcriptional activity of both MyoG and Mstn gene promoters. We show that TBX5 is upstream of Mstn, it binds to the promoter on specific TBE sites, and is able to upregulate Mstn promoter activation. In vivo, we show that MDX mice limb skeletal muscle tissues show elevated levels of TBX5, MYBBP1a and MSTN expression which suggest that the TBX5 pathway is associated with and indicative of the onset of proliferation and regeneration in MDX skeletal muscle tissue. Chapter 3 discusses the role of TBX5 in proliferation and regeneration of skeletal muscle cells by identifying that TBX5 binds to CcnD2 promoter and upregulates its activation which is a known cell cycle gene critical in cell proliferation and survival. Moreover, we identify GATA4 as a TBX5a cofactor in myoblast proliferation and show synergistic activation of Ccnd2 promoter by cooperative TBX5a and GATA4 action. We further show that Tbx5 heterozygote mice exhibit decreased levels of CCND2 and other proliferation markers, as well as decreased expression of PAX7 (marker of satellite cells) compared to WT skeletal muscle tissues. We also show that the heterozygous loss of Tbx5 impairs the process of regeneration in a cardiotoxin-induced injury model in mouse limb tissues. Tbx5 heterozygote mice exhibit less proliferation and impaired regeneration 4 days after injury, followed by decreased formation of regenerated fibers by 7 days post-injury compared to the wildtype mice skeletal muscle tissues; suggesting that TBX5 function is important in maintaining adult muscle regenerative capacity. Together, this study has characterized TBX5 isoforms and identified novel TBX5 protein partners and targets in the skeletal muscle cells and sheds light on TBX5 regulatory mechanism in proliferation and differentiation of skeletal muscle cells and its potential implications in HOS and other muscular diseases.
Keywords: TBX5; Skeletal muscle; Proliferation; Differentiation; Regeneration; Muscular disorders